PEMANFAATAN LIMBAH KULIT KELAPA SEBAGAI CAMPURAN MATERIAL PAVING BLOCK BAGI USAHA KECIL MENENGAH DI DESA BERNUNG KABUPATEN PESAWARAN - Fery Hendi Jaya; zesty miranda; M. Fikri Akbar; Farendra Subekti (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2024)
Nowadays we have found lots of variations or various kinds of community innovations related to the needs of the community itself, so that the community is trying to make it easier so that their needs are met, especially in the current economic situation, the community which has just experienced economic improvements after the Covid-19 pandemic. The purpose of this service is to increase public knowledge and understanding of the benefits of coconut shell waste as a mixture for making paving blocks. Currently, as the population increases, physical development is increasing, and the need for building materials is also increasing. For example Paving blocks are usually used for coating soil, such as vehicle parking lots, yards, alleyways, etc. Basically, paving blocks are only designed to withstand compressive strength. However, it cannot be denied that paving blocks will also receive tensile forces as a result of unstable soil conditions or imperfect installation. Most of the damage that occurred in the field was broken in the middle, not destroyed. The large amount of coconut shell waste that should be used as a basic ingredient for making paving block mixes. With the use of coconut shell waste as a mixture of materials, it is hoped that it can help the community as a building material so that it makes it easier and costs less.